71.6k views
2 votes
Question 43 please. I would also appreciate it if you could explain your steps. Thank you

Question 43 please. I would also appreciate it if you could explain your steps. Thank-example-1
User Ed Shee
by
5.2k points

1 Answer

5 votes

Answer:

D. p is multiplied by 2

Explanation:

43. We can simplify the formula a bit to better see the effect of changing 'a'.


p=((1)/(2)ary+a)/(12y)=(ary+2a)/(2(12y))=(a(ry+2))/(24y)

This tells you that for unchanging values of r and y, the value of p is proportional to the value of a. That is, the formula is of the form ...

p = ka . . . . for k=(ry+2)/(24y)

If a is multiplied by 2, p is multiplied by 2.

User Ivars
by
5.1k points